Industrial Air Pollution Leads to Adverse Birth Outcomes: A Systematized Review of Different Exposure Metrics and Health Effects in Newborns - Triin Veber; Usha Dahal; Usha Dahal; Katrin Lang; Kati Orru; Hans Orru; Hans Orru (Public Health Reviews, 2022)
Objectives: To review the evidence of associations between adverse birth outcomes (ABO) and industrial air pollution.Methods: Searches were conducted in PubMed, and Scopus databases, and additional articles were found from snowball search techniques. The included studies feature a study population of mothers with live-born babies exposed to industrial air pollutants, and they examine the effects of industrial pollutants on adverse birth outcomes—namely, low birth weight, term low birth weight, preterm birth, and small for gestational age.Results: Altogether, 45 studies were included in this review. Exposure to PM2.5, PAHs, benzene, cadmium, and mixtures of industrial air pollutants and living near an industrial area affect birth outcomes.Conclusion: This study concludes that industrial air pollution is an important risk factor for ABO, especially low birth weight and preterm birth. The strongest evidence is associations between ABO and air pollution from power plants and petrochemical industries. Understanding of specific chemicals that are critical to birth outcomes is still vague. However, the evidence is strongest for more specific air pollutants from the industry, such as PAH, benzene, BTEX, and cadmium.